2011
DOI: 10.1016/j.dcn.2011.03.004
|View full text |Cite
|
Sign up to set email alerts
|

How grossed out are you? The neural bases of emotion regulation from childhood to adolescence

Abstract: The ability to regulate one’s emotions is critical to mental health and well-being, and is impaired in a wide range of psychopathologies, some of which initially manifest in childhood or adolescence. Cognitive reappraisal is a particular approach to emotion regulation frequently utilized in behavioral psychotherapies. Despite a wealth of research on cognitive reappraisal in adults, little is known about the developmental trajectory of brain mechanisms subserving this form of emotion regulation in children. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
101
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(113 citation statements)
references
References 96 publications
10
101
1
1
Order By: Relevance
“…Moreover, during childhood, cognitive control-related PFC activity is known to undergo substantial developmental changes (Durston and Casey, 2006;Rubia, 2012). In fact, prior fMRI reappraisal studies in children and adolescents found both enhanced and reduced PFC activity (Lévesque et al, 2004;McRae et al, 2012;Pitskel et al, 2011) and reappraisal-related activity in the left inferior frontal gyrus was reported to increase with age, whereby children aged 10-13 years did not yet show enhanced activity (McRae et al, 2012). Based on these developmental changes, it is conceivable that some results are confounded by analyses across a rather broad age range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, during childhood, cognitive control-related PFC activity is known to undergo substantial developmental changes (Durston and Casey, 2006;Rubia, 2012). In fact, prior fMRI reappraisal studies in children and adolescents found both enhanced and reduced PFC activity (Lévesque et al, 2004;McRae et al, 2012;Pitskel et al, 2011) and reappraisal-related activity in the left inferior frontal gyrus was reported to increase with age, whereby children aged 10-13 years did not yet show enhanced activity (McRae et al, 2012). Based on these developmental changes, it is conceivable that some results are confounded by analyses across a rather broad age range.…”
Section: Discussionmentioning
confidence: 99%
“…Previous fMRI experiments in children and adolescents converge by showing increased activity in prefrontal and increased or decreased activity in emotion generating regions during reappraisal. Moreover, these studies consistently demonstrate age-related changes particularly in prefrontal structures (Lévesque et al, 2004;McRae et al, 2012;Pitskel et al, 2011), although the detailed pattern of results is quite inconsistent. So, children's neural networks underlying reappraisal overlap with those of adults, but data of children are still rare and age-related changes remain to be specified.…”
Section: Q2mentioning
confidence: 94%
“…Specifically, it was observed that age-related changes in the amygdala response during reappraisal are mediated by a vlPFC region implicated in semantic and cognitive control processes (Hinke et al 1993;Huang et al 2002;Thompson-Schill et al 2005;Badre and Wagner 2007) that has previously been shown to support developmental changes in "cold" cognitive control processes such as response inhibition (Durston et al 2002;Tamm et al 2002;Velanova et al 2008). Three prior developmental neuroimaging studies examining reappraisal of aversive stimuli obtained conflicting results about whether age predicted increased lateral prefrontal recruitment or diminished amygdala responses (Pitskel et al 2011;McRae et al 2012;Silvers et al 2015). These conflicting results could be due to the fact that age-related changes in the amygdala response are influenced by individual variability in vlPFC recruitment that may not be identified as easily in standard main effect analyses, but may be more easily observed through the use of statistical mediation.…”
Section: A Model Of Negative Emotion Regulation In the Developing Brainmentioning
confidence: 98%
“…Prior work has adopted 1 of 2 approaches when investigating prefrontal-amygdala dynamics in reappraisal. One approach has been to use correlational analyses to identify between-participant differences in prefrontal recruitment that predict less amygdala activation (Urry et al 2006;Johnstone et al 2007;Pitskel et al 2011). Another approach has been to use functional connectivity analyses to identify prefrontal regions that dynamically track within-participant changes in amygdala activation (Banks et al 2007).…”
Section: A Model Of Negative Emotion Regulation In the Developing Brainmentioning
confidence: 99%
See 1 more Smart Citation